Rode Valken kerstfeest in gebouw de Rietwijker, Amsterdam. Zie ook detailfoto van Frits de Jongh: BG A6/908
Rode Valken kerstfeest in gebouw de Rietwijker, Amsterdam. Zie ook detailfoto van Frits de Jongh: BG A6/908.